Evolucija lesnih rastlin - Torelli, Niko (Les (Ljubljana), 1998)
Transition from gymnosperm to angiosperm occured during the Jurassic and lower Cretaceous Periods. The earliest fossils of angiosperm leaves and wood date to about 125-130 million years. The oldest known fossil flower is about 120 million years old. Monocots and dicots separated into two evolutionary lineages less than 120 million years. Vessel elements evolved from tracheids and are polyphyletic in origin. Mayor trends of xylem evolution as well the features related and not related to this trends are described. Shortening of fusiform cambial initials in angiosperms was accompanied by the extracambial intrusive elongation of fibres. The transition from the woody stem to the herbaceous typ is discussed.
Keywords: botanika; Rhododendron-Park Bremen; rastline; evolucija; filogenija; kritosemenke